2009
DOI: 10.1111/j.1468-3083.2009.03306.x
|View full text |Cite
|
Sign up to set email alerts
|

Terbinafine (250 mg/day): an effective and safe treatment of cutaneous sporotrichosis

Abstract: This study suggests that 250 mg/day terbinafine is an effective and well-tolerated alternative to drug therapy of cutaneous sporotrichosis in a population in which itraconazole use is not possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 17 publications
1
32
0
Order By: Relevance
“…Five patients from South Africa were cured with 250 mg twice daily administered for 8 to 37 weeks (mean, 18; median, 14) [40], and 12 of 16 Japanese patients were cured with 125 mg daily (although the dose was raised to 250 mg daily in two of them), administered for a range of 10 to 21 weeks [36]. Also, 86% of 45 Brazilian patients with contraindications for itraconazole treatment were cured with terbinafine, 250 mg daily [41]. Favorable responses with dosing lower than 500 mg twice daily could be explained by involvement of different Sporothrix species or strains.…”
Section: Terbinafinementioning
confidence: 97%
“…Five patients from South Africa were cured with 250 mg twice daily administered for 8 to 37 weeks (mean, 18; median, 14) [40], and 12 of 16 Japanese patients were cured with 125 mg daily (although the dose was raised to 250 mg daily in two of them), administered for a range of 10 to 21 weeks [36]. Also, 86% of 45 Brazilian patients with contraindications for itraconazole treatment were cured with terbinafine, 250 mg daily [41]. Favorable responses with dosing lower than 500 mg twice daily could be explained by involvement of different Sporothrix species or strains.…”
Section: Terbinafinementioning
confidence: 97%
“…The three studies using terbinafine in human patients demonstrated a good efficacy for doses ranging from 250 to 1,000 mg/day (43,73,74). A study comparing 250 mg/day of terbinafine to 100 mg/day of itraconazole resulted in healing in 92.7% and 92% of patients, respectively, indicating terbinafine to be an effective and well-tolerated option for the treatment of cutaneous sporotrichosis (73).…”
Section: Treatmentmentioning
confidence: 99%
“…In a comparative study, Song et al [59] demonstrated similar efficacy and safety of itraconazole pulse regimen (200 mg bd for 1 week with a 3 week break) to the continuous (100 mg bd) regimen. Terbinafine 250 mg daily is equally efficacious as itraconazole 100 mg daily for cutaneous sporotrichosis [60] and has also been shown to be a well tolerated alternative in cases when itraconazole is contraindicated or resulted in significant drug interactions [61]. Ketoconazole is not recommended because of its inferior efficacy and significant adverse effects [54].…”
Section: Sporotrichosismentioning
confidence: 98%